2001
DOI: 10.1161/hc3001.092040
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Enhances Cytokine-Induced Apoptosis in Vascular Smooth Muscle Cells and Reduces Intimal Hyperplasia

Abstract: Background-Cytokines induce apoptosis in vascular disease lesions through enhancement of inducible nitric oxide (NO) synthase (iNOS) activation. The thiazolidinediones, novel insulin-sensitizing agents, have been demonstrated to modulate cytokine-induced NO production. We have investigated the role of pioglitazone in the apoptosis of vascular smooth muscle cells (VSMCs) in vitro and developed intimal hyperplasia in vivo. Methods and Results-Pioglitazone (0.1 to 10 mol/L) significantly enhanced cytokine-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 32 publications
(33 reference statements)
5
56
0
Order By: Relevance
“…However, in this study that uses EPCs, it is difficult to induce detrimental effects on cells, including the adhesion ability, with cytokines, including a combination of IL-1␤, interferon-␥, and TNF-␣. We have confirmed that cellular damage/apoptosis can be induced in vascular smooth muscle cells, and CECs can be induced by these cytokines (3). Cytokines such as TNF-␣ have been reported to have both beneficial and detrimental effects on certain cell types including mesenchymal stem cells and EPCs (40,46).…”
Section: Ape1 Enhances the Homing Of Epcs To Injured Vascular Wallssupporting
confidence: 68%
“…However, in this study that uses EPCs, it is difficult to induce detrimental effects on cells, including the adhesion ability, with cytokines, including a combination of IL-1␤, interferon-␥, and TNF-␣. We have confirmed that cellular damage/apoptosis can be induced in vascular smooth muscle cells, and CECs can be induced by these cytokines (3). Cytokines such as TNF-␣ have been reported to have both beneficial and detrimental effects on certain cell types including mesenchymal stem cells and EPCs (40,46).…”
Section: Ape1 Enhances the Homing Of Epcs To Injured Vascular Wallssupporting
confidence: 68%
“…[21][22][23][24] Furthermore, TZDs induce apoptosis of VSMCs via p53 and Gadd45. 25,26 Angiotensin II (AngII) plays an important role in vascular remodeling via the AngII type 1 receptor (AT1R) and accelerates atherosclerosis. Although AngII induces transcriptional suppression of PPARγ, activation of PPARγ inhibits AT1R gene expression at a transcriptional level in VSMCs.…”
Section: Pparγ and Atherosclerosismentioning
confidence: 99%
“…The region between À234 and À81, therefore, contains critical elements required for activation of the PPARg ligands inhibit intimal hyperplasia in rat models of restenosis after balloon injury in both insulin-resistant and insulin-sensitive animals. 1,[27][28][29][30] Concomitant with the phenotypic shift from quiescent VSMC resident in the uninjured vessel wall to proliferating VSMC present in the neointima, there is a substantial upregulation of PPARg expression. 3,9 High-level expression of functional PPARg in intimal VSMC, therefore, provides an attractive therapeutic target to exploit the antiproliferative and proapoptotic properties of PPARg ligands.…”
Section: Pparc-mediated Modulation Of Proliferation and Apoptosis D Bmentioning
confidence: 99%